2003
DOI: 10.1034/j.1600-0412.2003.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal electrical stimulation of the pelvic floor: A randomized feasibility study in urinary incontinent elderly women

Abstract: Although the number of enrolled women was very small this study shows that: 1. Treating elderly women with vaginal ES of the pelvic floor has a high physical and emotional cost for the individual. 2. The effectiveness of ES of the pelvic floor in urinary incontinent elderly women is low. 3. There is no great discrepancy between objective amelioration (PAD test) and subjective amelioration (PRAFAB score/quantity of urinary leakage), if the objective improvement is adequately defined. 4. It is not reasonable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 18 publications
0
47
0
7
Order By: Relevance
“…no urine loss. However, the studies of Luber and Wolde-Tsadik 26 and Spruijt et al 27 using the pad test showed no significant difference in urine loss in women with SUI treated with NMES compared with the control group (placebo NMES) or Kegel exercises.…”
Section: Discussionmentioning
confidence: 96%
“…no urine loss. However, the studies of Luber and Wolde-Tsadik 26 and Spruijt et al 27 using the pad test showed no significant difference in urine loss in women with SUI treated with NMES compared with the control group (placebo NMES) or Kegel exercises.…”
Section: Discussionmentioning
confidence: 96%
“…Four trials to treat mixed urinary incontinence were included with a total of 143 patients (35)(36)(37)(38). Most patients in the trials were close to 50 years of age.…”
Section: Mixed Urinary Incontinencementioning
confidence: 99%
“…Although electrical stimulation has been shown to be effective in treating the symptoms of OAB, this effect can not occur so markedly in older population. Spruijt (39) showed low ef icacy of electrical stimulation and perineal exercises, when applied to the elderly, correlating these indings about aging to hormonal changes and great emotional impact. The UI in elderly is considered multifactorial, including changes in body tissues, anatomy, lifestyle and personal characteristics.…”
Section: Resultsmentioning
confidence: 99%